Behavioral Aspects Approaches in Encouraging Green Accounting Practices for MSMEs In West Sulawesi: Spirituality and Kalindaqdaq Perspective - Galib, Abdul; Wulandari, Futri Ayu; Ariyandani, Nur (Economics and Business Journal (ECBIS), 2024)
The issue of environmental sustainability for the UMKM sector is new considering that the emphasis on green accounting practices has focused on large companies that are listed as publicly listed companies. In the context of sustainable business practices, policies that specifically promote the implementation of green accounting among UMKM are still limited. The purpose of this study is to identify and examine the determinants of behavioural aspects in encouraging awareness of UMKM green accounting practices in West Sulawesi from the perspective of spirituality and Kalindaqdaq Mandar culture. The research method used in this research is a mix method with a concurrent model to analyse quantitatively and qualitatively simultaneously. The quantitative method with the Partial Least Square (PLS) approach was conducted to test the Theory of Planned Behaviour (TPB) in green accounting practices. The results of this study indicate that UMKM players in West Sulawesi have not yet carried out green accounting practices but in general they already have the intention to practice green accounting. Another finding is that government policies can encourage green accounting practices so that the government needs to pay attention to the importance of regulations governing the obligation of UMKM players to carry out green accounting practices, awareness of green accounting practices that are early owned by UMKM can encourage the practice of awareness of green accounting practices in the future